Long distance laying technology of casing for connected roadway directional borehole in underground coal mine and its application - Kuiying, Gao; Guo, Li; Zhibin, Li; Haitao, Mo; Yijun, He; Xiongwei, Li (Frontiers in Built Environment, 2025)
Aiming at the problem of long distance laying of casing for connected roadway directional borehole in underground coal mine, the bending capacity and passing capacity of casing were calculated and analyzed with the large diameter casing of Ф219 × 8.94 mm as the research object. The stress situation in the process of casing running was studied, and the supporting pipe jacking machine was developed and the engineering test was carried out. The results show that the limit dog leg of the casing string is 5.512°/30 m. The smaller borehole diameter has high requirements for dogleg control, and the larger borehole diameter increases the drilling difficulty. The preferred borehole diameter is 330 mm. The casing laying scheme of ' drill machine pulling back + pipe jacking machine pushing ' is put forward. The casing pushing and pulling process should be matched with thrust and tension. Focus on the design of horizontal telescopic guide rail propulsion system and mobile centralizer and clamping release system, the supporting pipe jacking machine was developed. The engineering test was carried out in the directional long borehole between Daliuta Mine and Huojitu Mine. The casing running and cementing achieved good results. The research results can provide reference for the implementation of similar projects.